Kleine-Levin Syndrome: An Autoimmune Hypothesis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Clinical, polysomnographic, CSF, CT, and MRI records and genotype data of 30 unrelated patients with Kleine-Levin syndrome (KLS) and their families were studied at Hopital Gui-de-Chauliac, Montpellier, France, and other sleep centers.